1982
DOI: 10.1002/pssa.2210740212
|View full text |Cite
|
Sign up to set email alerts
|

Defect Structure of Cu-Doped Cadmium Selenide

Abstract: High‐temperature conductivity and copper solubility in CdSe is measured over the range 600 to 900°C as a function of temperature and cadmium and selenium vapour pressure. It is found that in cadmium vapour (pCd > 10−1 atm) below 750°C the main part of copper is in electrically inactive form and with increasing temperature transfers to the electrically active interstitial form Cu i˙ The activation energy of transference is found to be (2.0 ± 0.28) eV. In cadmium vapour the incorporation of copper occurs by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

1988
1988
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 9 publications
2
4
0
Order By: Relevance
“…12,13,18,25,26 Opik et al 12 performed resistivity measurements on CdSe crystals doped with 7 × 10 18 atoms cm -3 of copper by the surface method and reported a carrier activation energy of 1.02 eV which is similar to the value of 1.1 eV observed in this work. 12,13,18,25,26 Opik et al 12 performed resistivity measurements on CdSe crystals doped with 7 × 10 18 atoms cm -3 of copper by the surface method and reported a carrier activation energy of 1.02 eV which is similar to the value of 1.1 eV observed in this work.…”
Section: Hall and Resistivitysupporting
confidence: 83%
See 3 more Smart Citations
“…12,13,18,25,26 Opik et al 12 performed resistivity measurements on CdSe crystals doped with 7 × 10 18 atoms cm -3 of copper by the surface method and reported a carrier activation energy of 1.02 eV which is similar to the value of 1.1 eV observed in this work. 12,13,18,25,26 Opik et al 12 performed resistivity measurements on CdSe crystals doped with 7 × 10 18 atoms cm -3 of copper by the surface method and reported a carrier activation energy of 1.02 eV which is similar to the value of 1.1 eV observed in this work.…”
Section: Hall and Resistivitysupporting
confidence: 83%
“…Robinson et al 13 reported that this level was a defect involving native acceptors and identified this as the main sensitizing center in their copper doped films but found no evidence of any association of this level with the copper level they also observed. Conversely, Ermolovich et al 4 reported an increase in the magnitude of the luminescence peak associated with this level in their copper doped films relative to their undoped films while, Opik et al 12 postulated that the copper acts as an acceptor in the CdSe by forming a complex with this level.…”
Section: Identification Of the Copper Centermentioning
confidence: 96%
See 2 more Smart Citations
“…S2 and Supplementary Table S1). Cu þ is a common interstitial dopant in CdSe 19,20 . It is known that such dopants do not necessarily disrupt the excitonic band or the ARTICLE NATURE COMMUNICATIONS | DOI: 10.1038/ncomms3933 overall crystallographic structure of CdSe 18,19 , which is consistent with our optical and electron diffraction measurements.…”
Section: Resultsmentioning
confidence: 99%